Mechanical properties and performance of engineering ceramics and composites : a collection of papers presented at the 29th International Conference on Advanced Ceramics and Composites, January 23-28, 2005, Cocoa Beach, Florida - International Conference on Advanced Ceramics and Composites 2005 : Cocoa Beach, Fla.); Lara-Curzio, Edgar, 1963-; Zhu, Dongming; Kriven, Waltraud M. (Westerville, Ohio : American Ceramic Society, 2005)
Over 45 papers included in this collection present the latest advances in research and development on the processing, mechanics and mechanical properties of advanced ceramics and composites.
FRACTURE AND DAMAGE OF CERAMICS AND COMPOSITES. -- Computer Modeling of Crack Propagation Using Fractal Geometry. -- Geometry of Edge Chips Formed at Different Angles. -- Threshold Stress During Crack-Healing Treatment of Structural Ceramics Having the Crack-Healing Ability. -- Ablation of Carbon/Carbon Composites: Direct Numerical Simulation and Effective Behavior. -- Modeling of Deformation and Damage Evolution of CMC With Strongly Anisotropic Properties. -- MATERIALS CHARACTERIZATION, NDE AND NOVEL TECHNIQUES. A Novel Test Method for Measuring Mechanical Properties at the Small Scale: The Theta Specimen. -- Nondestructive Evaluation of Machining and Bench-Test Damage in Silicon-Nitride Ceramic Valves. -- NDE for Characterizing Oxidation Damage in Reinforced Carbon-Carbon Used on the NASA Space Shuttle Thermal Protection System. -- Determination of Elastic Moduli and Poisson Coefficient of Thin Silicon-Based Joint Using Digital Image Correlation. -- Use of Rupture Strength Testing in Examining the Thermal Cycle Behavior of Various Types of Planar Solid Oxide Fuel Cell Seals. -- Characteristics of Sealed Parts Under Internal Pressure in Super High Pressure Mercury Discharge Lamps. -- PROCESSING AND PROPERTIES OF CERAMICS. Synthesis of Titanium Aluminate-Alumina Compositions for Low TEC Applications. -- Structuring Ceramics Using Lithography. -- The Notion of Densification Front in CVI Processing with Temperature Gradients. -- Fabrication and Characterization of MGC Components for Ultra High Efficiency Gas Turbine. -- Comparison of Sodium Caprylate and Sodium Stearate and the Effects of Their Hydrocarbon Chain Lengths on Adsorption Behavior and Alumina Paste Rheology. -- Formulation of Additives for Water-Based Tape Casting of Ceramics. -- A Non-Linear Programming Approach for Formulation of Three-Component Ceramics as a Function of Physical and Mechanical Properties. -- Microstructural and Mechanical Properties of Directionally Solidified Ceramic in Al2O3-Al2TiO5 System. -- Study of the Relationship Between the Young's Modulus and Microstructure of Vacuum Plasma Sprayed Boron Carbide. -- Scalloped Morphologies of Ablated Materials. -- Mechanical and Thermal Properties of Non-Aqueous Gel-Cast Celsian and Sialon Ceramic Materials. -- Bend Stress Relaxation Creep of CVD Silicon Carbide. -- HARDNESS AND WEAR RESISTANCE OF CERAMICS. -- Mechanical Responses of Silicon Nitrides Under Dynamic Indentation. -- Scratch Resistance and Residual Stresses in Longitudinally and Transversely Ground Silicon Nitride. -- Improving the Damage-Resistance of Si3N4-Based Ball and Roller Bearing Components and Their Non-Destructive Evaluation. -- PROPERTIES OF FIBER-REINFORCED COMPOSITES. Comparison of Elevated Temperature Tensile Properties and Fatigue Behavior of Two Variants of a Woven SiC/SiC Composite. -- Tensile and Thermal Properties of Chemically Vapor-Infiltrated Silicon Carbide Composites of Various High-Modulus Fiber Reinforcements. -- Preparation and Properties of Dense SiC/SiC Composites. -- Fabrication of SiC/SiC with Dispersed Carbon Nano-Fibers Composite for Excellent Thermal Properties. -- Transpiration Cooling Structure Effects on the Strength of 3D-Woven SiC/SiC Composites Under Thermal Cycling. Constituent Properties Determination and Model Verification for Ceramic Matrix Composite Systems. -- Short-Fiber Reinforced CMCs: Potentials and Problems. -- LAMINATED CERAMICS AND PARTICULATE-REINFORCED CERAMICS. -- Ceramic Laminates with High Mechanical Reliability by Design. -- Methods of Residual Stress Analysis in Layer Composites and Their Application. -- Potential Use of Mullite-SiC Whiskers-SiC Particles Multi-Composite as High Temperature Springs. -- Brazing and Characterization of Advanced Ceramic Joints. -- Development of Joining and Coating Technique for SiC and SiC/SiC Composites Utilizing Nite Processing. -- Effect of Active Fillers on Ceramic Joints Derived from Preceramic Polymers. -- Numerical Analysis of Single Lap Jointed Ceramic Composite Subjected to Tensile Loading.
Includes bibliographical references and index.
Keywords: Ceramic materials -- Congresses; Ceramics -- Congresses; Composite materials -- Congresses